Morphometric characteristic of seagrass Thalassia hemprichii in the waters of Barrang Lompo island and Kodingareng Lompo island - Riskawati Putri; Mesalina Tri Hidayani; Nursyahran Nursyahran (Sekolah Tinggi Ilmu Pertanian Wuna, 2023)
Seagrass beds in the waters of Barrang Lompo Island and Kodingareng Lompo have their own characteristics, especially for the type of Thalassia hemprichii. The purpose of this study was to determine the morphometric characteristics of seagrass Thalassia hemprichii and the environmental conditions of the waters on Barrang Lompo Island and Kodingareng Lompo Island. This research was conducted in June-July 2022 in the waters of Barrang Lompo Island and Kodingareng Lompo Island. The research method used was purposive sampling. Morphometrics of seagrass Thalassia hemprichii on Barrang Lompo Island at station 1 average leaf length 10.88 cm, leaf width 1 cm, rhizome length 5 cm, root length 6.46 cm, number of roots 8. At station 2 leaf length measures 7.5 cm, leaf width 1 cm, rhizome length 7.84 cm, root length 6.64 cm and number of roots 5. Meanwhile on Kodingareng Lompo Island at station 1 the size of leaf length was 10.33 cm, leaf width 1 cm, rhizome length 4 cm , root length 4.33 cm and number of roots 5. At station 2 the size of leaf length was 9.63 cm, leaf width 1 cm, rhizome length 4.85 cm, root length 4 cm, number of roots 5. Morphometrics of seagrass Thalassia hemprichii on islands Barrang Lompo and Kodingareng Lompo islands did not show a significant difference. The environmental conditions of the waters on both islands are still in optimum conditions for seagrass growth for the parameters of current speed and brightness.